Influence of swift heavy ions irradiation on optical and luminescence properties of Y3Al5O12 single crystals - Pankratova, Viktorija; Butikova, Jelena; Kotlov, A.; Popov, Anatoli I.; Pankratov, Vladimir (Elsevier B.V, 2024)
Optical and luminescence properties of Y3Al5O12 (YAG) single crystals preliminary irradiated by swift heavy ions were studied. Swift heavy Xe ions with fluences ranging from 6·1010 to 2·1012 ions/cm2 were utilized for the irradiation of nominally undoped YAG single crystals. A stable strong induced absorption observed in the 200–600 nm spectral range correlates with the irradiation fluence. It is suggested that several centers are responsible for this induced absorption in YAG single crystals and their possible origin (F-type centers) is proposed and discussed. The swift heavy ions irradiation strongly modifies the luminescence properties of YAG, namely, the excitonic emission at liquid helium temperature is drastically suppressed in heavily irradiated crystals. © 2024 The Authors. --//-- This is an open-access article V. Pankratova, J. Butikova, A. Kotlov, A.I. Popov, V. Pankratov, Influence of swift heavy ions irradiation on optical and luminescence properties of Y3Al5O12 single crystals, Optical Materials: X, Volume 23, 2024, 100341, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2024.100341.
Vladimir Pankratov reports financial support was provided by University of Latvia Institute of Solid State Physics. Viktorija Pankratova reports financial support was provided by University of Latvia Institute of Solid State Physics. Anatoli I Popov reports financial support was provided by University of Latvia Institute of Solid State Physics. Aleksei Kotlov reports financial support was provided by DESY. If there are other authors, they declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.The work of Vladimir Pankratov is supported by the LZP grant 2020/2-0074. Viktorija Pankratova and Anatoli I. Popov acknowledge LZP grant 2023/1-0453. The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. We acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. This research was carried out at P66 beamline at PETRA III. Beamtime was allocated for proposal I-20211648 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Ellipsometry; F-centers; Swift heavy ions; Synchrotron radiation; VUV luminescence spectroscopy; YAG